The Community Structure of Phytoplankton in Seagrass Ecosystem and its Relationship with Environmental Characterstics - Gede Iwan Setiabudi; Dietriech G. Bengen; Hefni Effendi; Ocky Karna Radjasa (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
The aimed of this study was to determine the plankton communities and its relationship with the chemical and physical condition in seagrass ecosystem at Pegametan Bay. The composition and abundance of plankton were observed in the sea water underneath the surface and were identified based on the guideline of Illustration of the Marine Plankton of Japan. The water quality was measured in situ using WQC HI 9829. The water sample was measured using closed reflux spectrometry for COD, TOC analyzer for DOC and APHA 2102 (4500) method for Nt and Pt. There are 27 species of plankton identified, which can be classified into three groups. Diatom group consists of 18 species with a 74.56% abundance. The non-litoral group consists of 6 species with a 23.35% abundance. Moreover, dinoflagellate group consist of 3 species with a 2.09% abundance. An abundance of plankton greater than 104 cell.L-1 was found in diatome group (Nitzschia sp., Thalassiosira sp., Chaetoceros sp., Flagillaria sp., Thalassiothrix sp., and Melosira sp.) and non-litoral group (Oscillatoria sp. and Spirogyra sp.). The abundance of those species indicated the algae bloom phenomenon. Dinophysis sp. was also identified, which was harmful algal blooms.How to CiteSetiabudi, G. I., Bengen, D. G., Effendi, H., Radjasa, O. K. (2016). The Community Structure of Phytoplankton in Seagrass Ecosystem and its Relationship with Environmental Characterstics. Biosaintifika: Journal of Biology Biology Education, 8(3), 257-269.